Between land and sea: the transformation of the communication system of ukrainian sailors' wives. - Stoianova , Halyna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Research objective. This article analyses the transformation of the communication system of Ukrainian sailors' wives during the Soviet and post-Soviet periods. The research aims to identify changes in the forms and practices of communication among sailors' wives and fiancées in the context of socio-historical transformations.The research methodology is based on reflection on personal experience and a combination of qualitative methods – interviews and field observations in the families of sailors in Odessa – with an analysis of specialised Internet resources (forums, social networks, online communities). The use of approaches from social anthropology and gender studies made it possible to trace how communication among sailors' wives serves not only as a tool for maintaining family ties, but also as a factor in the formation of a special female subculture based on shared experiences of waiting, solidarity, and adaptation to the specifics of the maritime lifestyle.The scientific novelty lies in the introduction of the author's field materials into scientific circulation, which highlight the peculiarities of communication among Odessa sailors' wives, as well as in an attempt at a comparative analysis of Soviet and modern digital forms of communication. It is demonstrated that communicative changes reflect not only technical progress but also the transformation of women's strategies for overcoming separation, organising time, and preserving identity in a globalised world.The topic's relevance stems from the under-representation of sailors' wives as a distinct social group in Ukrainian humanitarian knowledge. Despite the existence of publications on professional communication among sailors, their wives remained outside the analytical field, which made it impossible to comprehensively understand the maritime environment as a complex of interrelated practices.Conclusions. The study found that Soviet forms of communication among sailors' wives (telegrams, radiograms, letters, meetings in ports) have given way to modern digital means of communication (mobile phones, the internet, and social networks). These innovations not only made it easier to maintain ties with sailors but also contributed to the formation of a special female subculture based on solidarity and the unique experience of waiting.